Case Report: Recurrent phyllodes tumor of the breast with progressive malignant transformation - Wang, Chuanyan; Wang, Shangui; Wang, Jiao; Dong, Ya; Chi, Yuhua; Wang, Yanbing (Frontiers in Oncology, 2025)
Phyllodes Tumor of the Breast (PTB) is a rare fibroepithelial tumor often misdiagnosed as fibroadenoma, leading to delayed or incorrect treatment. Although most PTBs are benign, some cases exhibit recurrent growth and progression to malignant forms. This report presents a 52-year-old female patient with PTB, who experienced multiple recurrences since her initial surgery in 2012, with the pathological grade gradually progressing from benign to borderline and ultimately malignant, characterized by heterologous osteosarcomatous differentiation. The tumor showed high heterogeneity and rapid progression. The final diagnosis was malignant phyllodes tumor of the breast with focal osteosarcomatous stromal components. Immunohistochemistry revealed a significant increase in the Ki-67 index from 8% to 70%, MDM2 positivity, and abnormal p53 expression, suggesting molecular transformation mechanisms. The patient underwent a modified radical mastectomy and three cycles of postoperative systemic chemotherapy with a combination of ifosfamide and cisplatin, which was well-tolerated. Thirty-six months after surgery, there was no recurrence or metastasis, and the disease remained stable. This case highlights the progression of PTB from benign to malignant and suggests that elevated Ki-67 and abnormalities in MDM2/p53 could serve as potential molecular markers. For patients with multiple recurrences or heterogeneous PTB components, individualized treatment strategies are recommended, with reference to soft tissue sarcoma protocols to optimize prognosis.